(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Use of the TinO2n-1 electrode for water electrolysis process promotes the destruction of organic matter as shown by the changes in permanganate index different values of electrolysed and non electrolysed solution. Using the TinO2n-1 electrode in the electrolysis process with the presence of chlorine and bromine ions can create a lasting disinfectant effect that was demonstrated by the sharp decrease in the number of bacterial colony forming units in electrolysed solutions. Using the TinO2n-1 electrode in the electrolysis process with the presence of iodine ions can create a bacteriostatic effect which was maintained for at least 10 days in electrolysed solutions